An Application of Chalcogenide Alloy Other than Storage Memory Field - Wang, Lei; Gong, Sidi; Yang, Cihui; Wen, Jing (Recent Patents on Nanotechnology, 2017)
Background: The necessity to handle mechanical functionality at nanoscale has recently motivated the prosperity of the nanoelectromechanical systems (NEMs). The fabrication of NEMS strongly depends on the so-called “topdown” techniques that are however limited by the resolution of electronbeam lithography. Meanwhile, the size of the NEMS needs to be shrunk continuously in order to further enhance the system performance. As a result, current research interest has been dedicated to “bottomup” techniques or even a hybridization of two aforementioned approaches, leading to the presence of the nanowire-based NEMs. Here, we presented some recent patent for nanowire-based NEMS. Methods: We investigate the resonant frequency and the frequency tuneability of the nanowire-based nanoelectromechanical system using Ge2Sb2Te5 media. By varying the nanowire dimensions, corresponding resonant frequencies and frequency tuneability are calculated using an established mechanical model. Results: We theoretically study the frequency tuneability of the nanowire-based NEMs using GST media. The resonant frequencies and the corresponding frequency tuneabilities for different nanowire dimensions are investigated using a developed mechanical model, and a previously established electrothermal model is performed to imitate the frequency tuning behavior of the system along with the phase-change phenomenon. By carefully controlling the amorphous fraction of the active region, a very high resonant frequency can be tuned within an ultra-high adjustable bandwidth. In addition, the merits of the phase-change memories including great scalability, low power consumption, fast transition time, and non-volatility can be also found on the proposed system. These results will open up a route for designing the next generation NEMs, and also pioneer a new application field for the GST media. Conclusions: Today phase-change materials have received a wide range of applications from nonvolatile memories to neuromorphic networks due to its unique combinations of structural, electrical, and thermal properties. However, as the mechanical properties of phase-change materials exhibits a remarkable difference between the amorphous and crystalline phases, the feasibility of continuously changing the resonant frequency of the nanowires based on phase-change materials becomes viable.
Keywords: Amorphization